ANALISIS BUDAYA ORGANISASI PEGAWAI DI KANTOR CAMAT RUMBAI PESISIR KOTA PEKANBARU - prihati, prihati; hernimawati, hernimawati (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2016)
The problems arising from the transfer of the office is the lack of innovation that made the apparatus districts in managing facilities and infrastructure, such as has not been doing renovations / office layout both internal and external. Then less stable governance for not referring to the spatial plan. The objectives to be achieved is to analyze how the organizational culture at the Head Office of Coastal Rumbai Pekanbaru and analyze barriers in organizational culture Rumbai Coastal District Office of Pekanbaru. Research done at the District Office Rumbai coastal city of Pekanbaru. The population in this study is the apparatus of the district office. They were selected because it was affordable. Camat serve as Key Informants. The sampling technique used is the census. Sources and types of data in this study are primary and secondary. In order to gather the necessary data, then used observation, interview and questionnaire. Data was analyzed by qualitative deskriftip. The research activities conducted in the organizational culture known Rumbai Coastal District Office has been running pretty well. Because in general, spilil state apparatus (ASN) in the District Rumbai Coastal already memahmi understanding organizational culture. Namely, a characteristic which is upheld by the organization and being a role model organization as a differentiator between one organization to another or organizational culture is also defined as the values and norms of behavior accepted and understood jointly by members of the organization as a basis in the rules of conduct contained within the organization.